Answer:
Explanation:
I'm taking this to mean
x/(x-2) + (x-1)/(x+1) = -1
Multiply through by (x - 2)*(x + 1) to get rid of the denominator on the left.
x(x + 1) + (x - 1)(x - 2) = -1 * (x - 2)(x + 1)
Remove the brackets on the left and right.
Be careful about the right side. Do it in two steps (or three)
x^2 + x + x^2 - 3x + 2 = - (x^2 - 2x + x - 2)
2x^2 - 2x + 2 = - (x^2 - x - 2)
2x^2 - 2x + 2 = - x^2 + x + 2
Bring the right side to the left
2x^2 - 2x + 2 + x^2 - x - 2 = 0
3x^2 - 3x = 0
Factor this
x*(3x - 3) =0
x = 0
3x - 3 = 0
Add 3 to both sides.
3x = 3
Divide by 3
x = 3/3
So either x = 0
or
x = 1
Just to confirm that that is correct, a graph is included which shows the x roots are 0 and 1